Effect of Hydroxyapatite Coatings on Corrosion Behavior for Biotype 316L SS Used in Orthopaedic Applications - Baghdad Science Journal (مجلة بغداد للعلوم)
Electrochemical corrosion of hydroxyapatite (HAP) coated performance depends on various parameters like applied potential, time, thickness and sintering temperature. Thus, the optimum parameters required for the development of stable HAP coatings was found by using electrophoretic deposition (EPD) technique. This study discusses the results obtained from open circuit potential-time measurements (OCP-time), potentiodynamic polarisation and immersion tests for all alloy samples done under varying experimental conditions, so that the optimum coating parameters can be established. The ageing studies of the coated samples were carried out by immersing them in Ringer’s solution for a period of 30 days indicates the importance of stable HAP coatings to prevent corrosion on the substrate material, so that enhancement to the biocompatibility will be increased.